Analysis of PAC (Minha Casa, Minha Vida Axis) in Valparaiso de Goias (GO): the production of a integrating/segregatingreality - Mello, Marcelo de; Souza, Bruno Augusto de (Sociedade & Natureza, 2018)
Valparaiso deGoiasemerged from adismemberment of themunicipality ofLuziania,in 1995. In the2010 Censusof IBGE, Valparaiso deGoiashad132,982inhabitants.In 2015, the official estimate indicated a significant population growth when the municipality reached the 153,255 inhabitants mark.This article analyzes the regional fragmentation process promoted in the course of integration of the national territory centered in Brasilia. As a central element, we highlight the residential segregation process, manifested in this municipality of Goias, from the impossibility of migrants take up residence in Brasilia. In this perspective, we investigated the program Minha Casa, Minha Vida, in order to verify their impact on segregating process, from the construction of Brasilia, dramatically affects the lives of those who had polarized life in the new capital of the republic.